Integrated Reporting Adoption Factors that Impact Financial Statement Accountability and Firm Performance: Natural RBV Theory Development Study in Indonesia - Adhi, Arief Surya; Azizah, Laila Oshiana Fitria (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine the factors that influence the adoption process of integrated reporting. The authors used the Natural Resource-Based View (RBV) theory as the main framework and developed its extension factors based on a literature review from various sources. Methodology: This study employs a correlational quantitative method and regression analysis tests using SPSS version 26.0 software. Research population consists of managers of micro, small, and medium enterprises (MSMEs) in Indonesia, with a sample size of 399 MSMEs managers selected through purposive sampling. Result: (1) green innovation variable has a significant influence on the adoption of integrated reporting by MSMEs, (2) green intellectual capital variable has a significant influence on the adoption of integrated reporting by MSMEs, (3) green supply chain management variable has a significant influence on the adoption of integrated reporting by MSMEs, (4) organizational capital variable has no influence on the adoption of integrated reporting by MSMEs, (5) regulatory pressure has no influence on the adoption of integrated reporting by MSMEs, (6) stakeholder pressure has a significant influence on the adoption of integrated reporting by MSMEs, (7) adoption of integrated reporting has a significant influence on the accountability of financial statements by MSMEs. Application/Originality/Novelty: The novelty of this study is in that it not only applies the Natural RBV theory to analysis, but also develops and directly tests the Natural RBV theory as a whole for MSMEs in Indonesia. Implication of this study can aid practitioners and managers in comprehending the significance of integrated reporting in business due to its numerous benefits. This study's implications are also valuable for experts, policymakers, and stakeholders who aim to maximize business operations, resulting in increased capital efficiency. In addition, these findings are beneficial not only for practitioners but also for academics and the development of science regarding business efficiency in the current industrial 4.0 era. Last, this study concludes by listing its limitations, recommendations, and acknowledgements.